Crianças produtoras de conteúdo audiovisual: a experiência da série infantil de TV Pintando a sétima arte - Graziella Cristina de Souza Luciano (2020)
This dissertation presents a study on the teaching of audiovisual in childhood and the production of content carried out by children, with children and for children. This research had as its object the experience of producing the children's TV series Pintando a Sétima Arte, carried out for Brazilian Public TVs, in 2016, in Belo Horizonte. This academic work has as premise the analysis of the creative journey of the group of 23 children producing the animated audiovisual content of this series, 13 animations, of 1 minute each. The analysis of the trajectory of this group was inspired by the Journeys of the Hero, of Joseph Campbell (2007) and the Writer, of Christopher Vogler (2015). This study investigates the concept of “Playing to make Cinema”, used in the series that combines documentary genres with animation. In this way, this dissertation may contribute to the expansion of knowledge about children producing audiovisual content, insofar as the little filmmakers of Pintando a Sétima Arte were able to make cinema playing and performed the exercise of thinking, to place themselves as objects of thought, to think about yourself, other people and the world.